Response of Imperata cylindrica to smothering by different Mucuna accessions - Ekeleme, F.; Chikoye, David (2000)
The Center for Cover Crops Information and Seed Exchange in Africa (CIEPCA) was established to support cover crops systems development for researchers, extension workers, and farmers in West Africa. CIEPCA has been in existence for approximately 3years. In that period, much has been accomplished. Among the highlights, we can cite the production of four newsletters (in English and in French), the dissemination of more than 5 tonnes of cover crops seeds, and the connection of 6 (out of 8) CIEPCA country representatives to the internet. Although an impact study has not been conducted, CIEPCA has certainly stimulated more efficient work on cover crops by stimulating information and seed exchange. In the next phase, CIEPCA will attempt to broaden its influence to the rest of Africa and strengthen global linkage.